Comparison of central corneal thickness measurements obtained by community optometrists to those obtained in secondary care. (November 2018) - Hughes, Laura; Loo, Cheng; Hogan, Brian; Tan, Huai; Tang, Ling; Tatham, Andrew
Abstract Purpose Corneal central thickness (CCT) is an important risk factor for glaucoma, which also influences intraocular pressure (IOP) measurements. Recently, all community optometrists in Scotland were provided with pachymeters. This study examined the accuracy of CCT measured by community optometrists compared to measurements in the glaucoma clinic. Methods A retrospective analysis of consecutive patients referred to the glaucoma clinic at a university hospital between June and November 2016. 142 of 715 (19.9%) patients had CCT measurements included in the referral, all of whom had repeat measurements in the glaucoma clinic. CCT was measured using the PachPen (Accutome Inc) which generates a CCT reading by automatically taking the average of up to 9 measurements. Measurements were compared using Bland-Altman analysis. Results CCT measured by community optometrists was slightly thicker than CCT in the glaucoma clinic (558.3 ± 41.5 vs. 552.6 ± 58.8 µm, P < 0.001), however the mean difference was only 13.8 ± 18.0 µm. In 223 of 284 eyes (78.5%), CCT measurements taken by community optometrists were within 20 µm of those obtained in the glaucoma clinic. 61 of 284 (21.5%) differed by >20 µm, 40 (14.1%) by >30 µm and 17 (6.0%) by >50 µm. There was no significant relationship between difference in CCT and IOP (−0.02, 95% CI −0.05 to 0.002, P = 0.077), gender (0.00, 95%CI −0.01 to 0.01, P = 0.805), or age (−0.01, 95% CI −0.08 to 0.06, P = 0.791). Conclusions There was good overall agreement between CCT measured by community optometrists and measurements obtained in the glaucoma clinic. The tendency for thicker CCT measurements by community optometrists may be due to more peripheral or non-perpendicular positioning of the pachymeter relative to the cornea.